PRINCIPAL COMPONENT ANALYSIS TO CHECK THE RELATION AMONG METEOROGICAL VARIABLES AND PM10 CONCENTRATION - Pozza, Simone Andrea; Nogarotto, Danilo Covaes [UNESP]; Garcia De Lima, Marla Rubia [UNESP] (Centro Federal Educacao Tecnologica Rio Grande Norte, 2020)
It's known that meteorological variables are directly related to the behavior of atmospheric pollutants. This work aimed at studying the influence of some meteorological variables (temperature, wind speed and relative humidity) in the variation of inhalable Particulate Matter concentration (PM10). The study used data collected from 2010 to 2014, in cities Americana, Jundiai, Paulinia and Piracicaba, located in Sao Paulo State. The relation among meteorological variables and PM10 was studied by Principal Component Analysis (PCA). It was obtained that three Principals Components explained more than 90% of data variability. Besides, it was found that PM10 and relative humidity had a stronger correlation (around 42%).
Keywords: Meteorological data; Particulate Matter; PCA